2015
DOI: 10.1016/j.jchf.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hypoperfusion Is Exaggerated With an Upright Posture in Heart Failure

Abstract: The reduction in CBF was exaggerated in the upright posture in HF patients and may increase the risk for subsequent cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
49
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 36 publications
(23 reference statements)
2
49
3
2
Order By: Relevance
“…In addition, gait speed was lower in the HFrEF subjects than in the healthy control subjects in the study of Frazer et al (11). However, it is difficult to attribute this finding solely to a lower supine CI, because it has been shown that flow to the cerebellar vermis increases from supine to standing (23) and, as previously noted, posterior flow was not assessed in the present study.…”
contrasting
confidence: 46%
See 4 more Smart Citations
“…In addition, gait speed was lower in the HFrEF subjects than in the healthy control subjects in the study of Frazer et al (11). However, it is difficult to attribute this finding solely to a lower supine CI, because it has been shown that flow to the cerebellar vermis increases from supine to standing (23) and, as previously noted, posterior flow was not assessed in the present study.…”
contrasting
confidence: 46%
“…Thus, cerebral inflow pressure in the upright position is less than the inflow pressure in the supine position. Because height and MAP between control subjects and HFrEF patients were similar, this effect is likely to be modest in the present experiment (11). However, HFrEF patients had a greater reduction in CI from supine to upright than control subjects (-12% vs. -0.44%; p ¼ 0.065), which would promote sympathoexcitation through a baroreceptormediated pathway with an increase in cerebrovascular resistance.…”
mentioning
confidence: 70%
See 3 more Smart Citations